Quality of Pharmacotherapy Lectures and Instructor Teaching Skills of the Pharm D Program in India: A Nationwide Survey - Bhagavathula, Akshaya Srikanth; Bandari, Deepak Kumar; Fialova, Daniela (Indian Journal of Pharmaceutical Education and Research, 2021)
Objectives: The present study aimed to evaluate the quality of pharmacotherapy (PT) lectures provided to PharmD students and to assess the teaching skills of the instructors. Materials and Methods: A cross-sectional study was conducted using a self-administered Instructional Skills Questionnaire (ISQ) instrument containing 39 items which was distributed to 1000 PharmD students who completed the PT courses during their third and fourth years of the PharmD program in India during the 2017/2018 academic year. Results: A total of 695 students completed the survey (response rate of 69.5%). The mean age (±standard deviation) was 21.9 ± 1.57) years, females 63% who completed their PT course during third- (49.1%) and fourth years (50.9%) of the PharmD program. The student participants indicated that their PT lecturer dedicated an average of 5.29 ± 3.39 hr/week to classroom teaching and 2.70 ± 3.29 hr to bedside teaching. Only a limited number of PharmD students agreed that their instructor explained the subject clearly (27.8%), gave PT summaries (32%), made the lectures enjoyable (33.8%) and discussed important topics (38.7%) with them. Overall, more than half (58%) of the students rated their quality of PT lectures as “average,” and only 28.3% of the PharmD students agreed that they achieved PT learning outcomes. Conclusion: Our study revealed that most student participants rated the quality of PT lectures as “average” resulting in sub-optimal achievement of their learning outcomes. PharmD programs should continue to review the quality of PT lectures and incorporate advanced pedagogical practices to improve PT instructor teaching skills.
Keywords: Clinical pharmacy; Pharmacotherapy; Evaluation; Education; Teaching; India